Thiabendazole uptake and persistence in lemons following postharvest dips at 50 degrees C - Schirra, M.; Angioni, A.; Ruggiu, R.; Minelli, E. V.; Cabras, P. (Chiriotti Editori, 1998)
Thiabendazole (TBZ) uptake and degradation rate in lemon fruits, following prestorage dipping at 50 degrees C in mixtures containing different amounts of fungicide, was compared with those measured after treatment at standard room temperature. TBZ residues were strictly dependent upon the amount of fungicide. Following 1,200 ppm TBZ dipping at 20 degrees C residue uptake in fruit was the same that would have been accumulated with ca. 150 ppm fungicide at 50 degrees C, a value that can be calculated due to the linear relationship between the residue in fruit after treatment and fungicide concentration TBZ residues showed great persistence during fruit storage: after 13 weeks at 8 degrees C and 1 week at 20 degrees C residues in fruit averaged ca. 70% of their initial values. In this study it was shown that it is possible to employ remarkably low amounts of TBZ (ca. 150 mg kg(-1)), when applied in combination with water at 50 degrees C, and keep the same residues of fruit treated at room temperature with high amounts of TBZ (1,200 mg kg(-1)).
Keywords: lemons; persistence; post-harvest; residues; thiabendazole